2018
DOI: 10.1177/1534650118808600
|View full text |Cite
|
Sign up to set email alerts
|

A Transdiagnostic Approach to the Treatment of Emetophobia: A Single Case Study

Abstract: The fear of vomiting (i.e., Emetophobia) causes substantial distress for affected individuals, and is associated with hypervigilance to somatic sensations, panic attacks, and behavioral avoidance. Interventions for Emetophobia have traditionally relied heavily on exposure to vomit, vomiting, and vomit-related cues, providing some challenges in identifying appropriate graded exposures for Emetophobia due to medical and hygiene concerns. Recent efforts have been made to treat psychopathology transdiagnostically;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Bogusch, Moeller, and O’Brien (2018) reported a case in which ACT was applied to emetophobia (it was the first case report of ACT for emetophobia). In addition, some case studies that used traditional CBT interventions for emetophobia have been reported (Dargis & Burk, 2018; Fix, Proctor, & Gray, 2016; Kobori, 2011). While Kobori (2011) involved a Japanese client, to the best of my knowledge, ACT and CBA have not been used for emetophobia in the Asian context.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Bogusch, Moeller, and O’Brien (2018) reported a case in which ACT was applied to emetophobia (it was the first case report of ACT for emetophobia). In addition, some case studies that used traditional CBT interventions for emetophobia have been reported (Dargis & Burk, 2018; Fix, Proctor, & Gray, 2016; Kobori, 2011). While Kobori (2011) involved a Japanese client, to the best of my knowledge, ACT and CBA have not been used for emetophobia in the Asian context.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Most case studies (e.g., Dargis & Burk, 2018; Fix et al, 2016; Kobori, 2011) are based on traditional CBTs or exposure models that assume emotions (e.g., fear and anxieties), cognitions, memories, and body sensations can be controlled and set a treatment goal to reduce symptoms. However, this type of traditional goal setting could be problematic.…”
Section: Treatment Implications Of the Casementioning
confidence: 99%
See 1 more Smart Citation
“…Die Emetophobie ist eine noch wenig erforschte Erkrankung [5]. Man weiß jedoch, dass die Phobie vor dem Erbrechen mehr Frauen als Männer betrifft [6]. Die Erkrankung verläuft meist chronisch und hält über Jahre oder ein Leben lang an [7].…”
Section: Introductionunclassified